POLA SALURAN PEMASARAN PADI SAWAH SEMI ORGANIK (Oryza sativa L) DI KELURAHAN SEI SELINCAH KECAMATAN KALIDONI KOTA PALEMBANG - Oktariani, Lisna; Wanna, Abdurrohim (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2021)
This research is located in Sei Selincah Village, Kalidoni District, Palembang City. This research aims to determine the profits received by semi-organic lowland rice farmers in Sei Seilincah Village Kalidoni District Palembang City to find out the marketing pattern of semi-organic lowland rice in Sei Selincah Village Kalidoni District Palembang City and to find out the most efficient semi-organic rice marketing channel in Sei Seilincah Village Kalidoni District Palembang City. The research method used is a survey method on semi-organic lowland rice farmers, while the sampling method used is a simple random sampling method with 15 respondents from a population of 25 farmers in 1 semi-organic lowland rice farmer group. The results obtained from this study are based on the average profit received by semi-organic lowland rice farmers in Sei Selincah Village of Rp. 5,495,400 with an R/C ratio of 1.75 > 1, which means that semi-organic lowland rice farming in Sei Selincah Village Kalidoni District Palembang City is economically profitable for farmers. There are 2 patterns of semi-organic lowland rice marketing channels in Sei Selincah Village. The marketing channel pattern that is mostly used by semi-organic lowland rice farmers in Sei Selincah Village is marketing channel I, which involves middlemen. In the marketing channel pattern I, there are 14 people who sell their organic paddy through middlemen, while the channel II pattern is the farmers directly sell it to consumers. Marketing channel II is a relatively more efficient marketing channel.